2009
DOI: 10.1007/bf03326130
|View full text |Cite
|
Sign up to set email alerts
|

Different techniques for the production of biodiesel from waste vegetable oil

Abstract: ABSTRACT:The production of biodiesel from waste vegetable oil offers a triple-facet solution: economic, environmental and waste management. The new process technologies developed during the last years made it possible to produce biodiesel from recycled frying oils comparable in quality to that of virgin vegetable oil biodiesel with an added attractive advantage of being lower in price. Thus, biodiesel produced from recycled frying oils has the same possibilities to be utilized. While transesterification is wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(138 citation statements)
references
References 127 publications
(196 reference statements)
3
130
0
5
Order By: Relevance
“…This indicated that the reaction had reached the saturation point and tended to favor the formation of gels that hinder the recovery of glycerol and decrease biodiesel yield (Encinar et al 2005). These results corresponded to those reported by Refaat, (2010) from which the best performance is obtained within a range of 0.5-1 %.…”
Section: Type and Catalyst Concentrationsupporting
confidence: 85%
See 3 more Smart Citations
“…This indicated that the reaction had reached the saturation point and tended to favor the formation of gels that hinder the recovery of glycerol and decrease biodiesel yield (Encinar et al 2005). These results corresponded to those reported by Refaat, (2010) from which the best performance is obtained within a range of 0.5-1 %.…”
Section: Type and Catalyst Concentrationsupporting
confidence: 85%
“…This technique requires precision and an adequate fatty acid profile of the oil sample (Table 3), for both, an excess as an insufficiency in the amount of catalyst added results in the formation of soaps (Refaat 2010). Considering that there is a direct relation between the FFA percentage and the amount of catalyst that has to be added to the reaction to compensate the acidity and its deactivation (Freedman et al 1986), alkaline neutralization was considered for the three samples as pre-treatment method for its effectiveness in lowering the FFA content, along with substantial quantities of mucilaginous substances, phospholipids and color pigments (Bhosle and Subramanian 2005;Sudhir et al 2007).…”
Section: Free Fatty Acids and Neutralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, in ethanolysis, they are more stable and severe, making it tough to separate and purify the esters. 33 In this context, this study evaluates the effect of soybean biodiesel produced via base catalysis and via the methanol and ethanol routes (hereinafter referred to as MR and ER, respectively) on the performance and emissions of formulations containing 10 and 20% (m/m) of biodiesel, using base diesel with low sulfur content and CN of 45 and 50. The soybean biodiesel composition produced via MR and ER was analyzed by gas chromatography with flame ionization detector (GC-FID) and by mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%